Small Scale Living and the Meaning of Home - Shelby Kiser (Undergraduate Research Journal for the Human Sciences, 2016)
In current United States housing trends, prices and square footage are rising as personal satisfaction and fulfillment decline. This is a result of people assuming that upgrading their living standards will provide instant gratification, but it may only lead to unhappiness. As our houses grow larger, so do our debts. During the most recent economic down turn a renewed interest in small scale living arose. People began seeing the value in downsizing, reducing debt, and living more sustainably. Evaluating the functional, environmental, economic, and psychological aspects of living small will help determine what challenges one will face by reconsidering how and where they live. With a deeper understanding of the connections and value of home, designers are able create dwellings that can positively influence the users. The potential impact starts with designers, therefore it is crucial to be educated and actively implementing this knowledge into designs. Beginning in the 1960's, people for simple and clutter-free living began advocating for the needs of the environment (Kahn & Welch, 2012). Since then living small has developed into much more. When the economy failed in 2008, this debt-free alternative to housing rose in popularity. The key to living small is about downsizing. Small scale living comes in many forms such as apartments, single family homes, and portable housing. Overall, downsizing to a smaller home is more than purging belongings and lowering your environmental impact, it takes mental awareness and a well-designed space. To appreciate how and why people are choosing to go tiny, we must understand the meaning of home. More extravagant and abundant space does not enhance one’s ability to feel at home or experience happiness. According to personal accounts, smaller homes provide a chance to relate to the space and discover the rewards of individualized homes that reflect identity, belonging, and self-expression (Grinberg, 2012).
Keywords: Tiny; Home; Measing; compact; living